REGULATION URGENCY OF CLIMATE CHANGE REFUGEES PROTECTION IN THE PERSPECTIVE OF INTERNATIONAL LAW - Wartini, Sri (Jurnal Dinamika Hukum, 2017)
change. The refugees are not categorized as refugees under the Refugees Convention 1951 since they are not caused by persecution. Thus, it is necessary to find out a solution based on international law to provide legal protection to them. Â The aim of the research is to analyse comprehensively the urgency of legal protection to the climate change refugees and to find out an appropriate legal protection to them. The paper is a normative juridical research by employing conceptual and comparative approach. The paper is analysed qualitatively and presented descriptively. The results show that: First,Â  there is a legal vacuum of the protection of climate change refugees ; second, it is necessary to regulate a legal protection to the climate change refugees since they become the victims of climate change.Key Words: Climate change refugees, global warming and urgency